Potential of MSMEs in the culinary sector: towards community-based economic empowerment - Ratnaningtyas, Heny; Taviprawati, Ervina; Wicaksono, Haryo; Aditya, Michael Khrisna (Universitas Widya Mataram, 2025)
MSMEs in Cibeber Village have great potential thanks to superior products from local natural resources, such as nutmeg, mangosteen, papaya and cloves. However, they face challenges in terms of marketing, access to capital, and development of production capacity. This research aims to analyze the potential and challenges faced by MSMEs in Cibeber Village using the SWOT approach, focusing on existing strengths, weaknesses, opportunities and threats. The research method used is a qualitative approach with data collection techniques through surveys, interviews, observations and documentation studies, with samples of culinary MSME actors operating for at least two years. Research findings show that the main strength of MSMEs in Cibeber Village is products based on unique local natural resources. However, weaknesses are related to limited production equipment and marketing that relies on traditional channels. Tremendous opportunities are opening up through market trends for environmentally friendly and organic products, but threats come from intense competition and falling raw material prices. SWOT analysis leads to a WT (Weaknesses-Threats) strategy, which focuses on increasing internal capacity, product diversification and strengthening marketing channels. In conclusion, MSMEs in Cibeber Village need to improve entrepreneurial skills, diversify products, and adapt to changing policies to optimize opportunities and reduce threats. The suggestion of this research is the importance of support from the government and related institutions to increase the capacity of MSMEs in a sustainable manner.